A mathematical model for flow maldistribution study in a parallel plate-fin heat exchanger. (5th July 2017) - Yang, Huizhu; Wen, Jian; Gu, Xin; Liu, Yuce; Wang, Simin; Cai, Wenjian; Li, Yanzhong
Highlights: A mathematical model to evaluate the flow maldistribution effect is proposed. A conventional, punched baffle and quasi- S header configurations are studied. A good synergy of flow rates for cold and hot fluids can enhance heat transfer. The thermal-hydraulic performance of a quasi- S header configuration is the best. Abstract: In this paper, a mathematical model is developed to quantitatively evaluate the effect of flow maldistribution in a multi-channel heat exchanger. A computational fluid dynamics (CFD) technology is used to obtain the fluid distribution in the core of heat exchanger, taking into account the effects of gross passages, headers and distributors, etc. Based on the CFD simulation profile, a heat exchanger model is then developed. A parallel plate-fin heat exchanger with N flow passages is divided into N sub-exchangers when only one fluid is in maldistribution mode or 2N-1 sub-exchangers when both fluids are in nonuniformity modes to guarantee the uniform flow patterns in each sub-exchanger. Based on ε -NTU theory, the effectiveness of the heat exchanger is calculated by modeling the heat exchanger as a parallel coupling of the sub-exchangers. The core pressure drop of the whole heat exchanger is taken as the average pressure drop of the sub-exchangers. The mathematical model combining with the achieved flow distribution was utilized to investigate the performance of the heat exchanger with conventional header configurations, a punched baffle header configuration and a quasi- S header configuration, respectively. Results indicated that a good synergy of flow rates for both cold and hot fluids in the adjacent sub-exchangers can effectively reduce effectiveness deterioration. The performance of the heat exchanger is improved by using the improved header configurations. And the performance with a quasi- S header configuration is the best. The proposed mathematical model provides a theoretical basis for multi-channel heat exchangers in solving the problem of flow maldistribution.